2020
DOI: 10.1128/aac.01103-20
|View full text |Cite|
|
Sign up to set email alerts
|

The Lymphocytic Scavenger Receptor CD5 Shows Therapeutic Potential in Mouse Models of Fungal Infection

Abstract: Background: Invasive fungal diseases represent an unmet clinical need that could benefit from novel immunotherapeutic approaches. Host pattern-recognition receptors (e.g., Toll-like receptors, C-type lectins or Scavenger receptors) that sense conserved fungal cell wall constituents may provide suitable immunotherapeutic antifungal agents. Thus, we explored the therapeutic potential of the lymphocyte class I scavenger receptor CD5, a non-redundant component of the antifungal host immune response that binds to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These results prompt further exploration of shCD5 as adjunctive immunotherapy to reduce the adverse effects associated with current anti-mycotic drugs without compromising their efficacy in case of drug resistance, and at the same time, to expand their antifungal spectrum. The lack of shCD5 efficacy, observed when treating C. albicans-infected immunodeficient NOD scid gamma (NSG) mice, supports the notion that an intact immune system is necessary for optimal survival following shCD5 infusion [55].…”
Section: Soluble Cd5 As Therapeutic Agent In Infectionmentioning
confidence: 85%
See 2 more Smart Citations
“…These results prompt further exploration of shCD5 as adjunctive immunotherapy to reduce the adverse effects associated with current anti-mycotic drugs without compromising their efficacy in case of drug resistance, and at the same time, to expand their antifungal spectrum. The lack of shCD5 efficacy, observed when treating C. albicans-infected immunodeficient NOD scid gamma (NSG) mice, supports the notion that an intact immune system is necessary for optimal survival following shCD5 infusion [55].…”
Section: Soluble Cd5 As Therapeutic Agent In Infectionmentioning
confidence: 85%
“…Such prophylactically infused mice also showed decreased toxicity score, peritoneal leukocyte infiltration, pro-inflammatory cytokine production, and liver myeloperoxidase activity [12]. Recent studies have further shown dose-and time-dependent therapeutic effects of rshCD5 infusion in mouse models of systemic infection by pathogenic fungal species (C. albicans and C. neoformans) [55]. Higher rshCD5-induced survival of lethally infected mice was concomitant with reduced fungal load, increased IFN-γ mRNA levels and increased lymphoid (NK and B) and myeloid (dendritic, macrophage and granulocyte) cell infiltration in primary target organs (i.e., kidney for C. albicans) [55].…”
Section: Soluble Cd5 As Therapeutic Agent In Infectionmentioning
confidence: 95%
See 1 more Smart Citation
“…Besides their lymphocyte immunomodulatory functions, CD5 and CD6 also exhibit broad pathogen-recognition receptor properties [4]. Accordingly, infusion of their human recombinant soluble ectodomains-rshCD5 and/or rshCD6-exerts prophylactic/ therapeutic potential in murine models of fungal, bacterial and parasitic infections [5][6][7][8].…”
Section: Brief Definitive Reportmentioning
confidence: 99%